Analysis Of The Role Of Management Accounting In Company Cost Control - Mumun Maemunah; Budi Rismayadi (SEAN Institute, 2024)
This study aims to analyze the role of management accounting in cost control in companies. Management accounting plays an important role in providing relevant and timely information for managers to make effective decisions regarding cost control. This study uses a descriptive approach with qualitative methods, where data is collected through literature studies and in-depth interviews with financial and accounting managers in several companies. The results of the study show that management accounting has a crucial role in controlling company costs through accurate planning, budgeting, and cost tracking. By analyzing various cost components, management accounting helps managers identify and manage expenses, set appropriate prices, and evaluate operational performance. In addition, management accounting supports strategic decision-making and resource optimization, enabling companies to achieve financial goals and increase profitability. Through strategies such as cost-benefit analysis, activity-based budgeting, performance measurement, and investment in technology, managerial accountants can provide insights to improve efficiency and create long-term value, strengthening a company's competitive position and supporting sustainable profit growth.